The role of human C5a as a non-genomic target in corticosteroid therapy for management of severe COVID19. (June 2021) - Das, Aurosikha; Rana, Soumendra
Graphical abstract: Illustrations of the C5a-prednisone complexes highlighting the range of estimated binding affinity. Highlights: C5a is the most potent proinflammatory peptide of the complement system. C5a significantly contributes toward the "hypercytokinaemia" loop. Neutralizing the aberrantly upregulated C5a can be beneficial for managing COVID19. C5a appears to be the non-genomic target of the synthetic corticosteroids. Prednisone binding to C5a with Kd ∼ 0.38 μM could be beneficial for COVID19. Abstract: Complement system plays a dual role; physiological as well as pathophysiological. While physiological role protects the host, pathophysiological role can substantially harm the host, by triggering several hyper-inflammatory pathways, referred as "hypercytokinaemia". Emerging clinical evidence suggests that exposure to severe acute respiratory syndrome coronavirus-2 (SARS-CoV2), tricks the complement to aberrantly activate the "hypercytokinaemia" loop, which significantly contributes to the severity of the COVID19. The pathophysiological response of the complement is usually amplified by the over production of potent chemoattractants and inflammatory modulators, like C3a and C5a. Therefore, it is logical that neutralizing the harmful effects of the inflammatory modulators of the complement system can be beneficial for the management of COVID19. While the hunt for safe and efficacious vaccines were underway, polypharmacology based combination therapies were fairly successful in reducing both the morbidity and mortality of COVID19 across the globe. Repurposing of small molecule drugs as "neutraligands" of C5a appears to be an alternative for modulating the hyper-inflammatory signals, triggered by the C5a-C5aR signaling axes. Thus, in the current study, few specific and non-specific immunomodulators (azithromycin, colchicine, famotidine, fluvoxamine, dexamethasone and prednisone) generally prescribed for prophylactic usage for management of COVID19 were subjected to computational and biophysical studies to probe whether any of the above drugs can act as "neutraligands", by selectively binding to C5a over C3a. The data presented in this study indicates that corticosteroids, like prednisone can have potentially better selectively (Kd ∼ 0.38 μM) toward C5a than C3a, suggesting the positive modulatory role of C5a in the general success of the corticosteroid therapy in moderate to severe COVID19.